A rare case of undifferentiated pleomorphic cardiac sarcoma mimicking as left atrium myxoma - Akshay Narendra Kotasthane; Chigullapalli Sridevi; Susheel Kumar Malani; Charusheela Gore (Heart India, 2025)
Primary cardiac tumors are a very uncommon clinical entity; their prevalence is believed to be between 0.001% and 0.030%, and about 25% of these masses are malignant. Cardiac myxoma, the most common cardiac tumor, is located in the left atrium (LA). Undifferentiated pleomorphic sarcoma is an uncommon malignant variant and commonly found in the LA. Atrial myxomas, which are benign tumors, frequently recur following excision. Recurrence has been linked to a number of theories, including incomplete excision, seeding during surgical excision, and multifocality. A myxoma’s malignant transformation has frequently been attributed to recurrence in the same location, which is comparatively rare. We report a case of pleomorphic sarcoma initially diagnosed as benign atrial myxoma and presented with recurrence. A middle-aged female with a chief complaint of chest pain and progressive dyspnea over 3 weeks. She had a history of left atrial myxoma and was operated for the same 3 years back at another hospital, which was uneventful. Transthoracic echocardiography revealed a large, fixed homogeneous mass in the LA adherent to inter interatrial septum and anterior mitral leaflet measuring 3.8 cm × 2.1 cm, moving into the left ventricle. It had a homogeneous echogenicity on echocardiography. After excision of mass, histopathology and immunohistochemistry (IHC) were suggestive of undifferentiated pleomorphic sarcoma. This case illustrates the challenges in the evaluation and diagnosis of primary cardiac tumor. Primary cardiac sarcoma is routinely misdiagnosed as atrial myxomas. It is difficult to identify the type of pleomorphic sarcomas on histology alone, and further, IHC is required. The prognosis of the patient with sarcoma is poor as compared to myxoma and mainly depends on completeness of resection, size of tumor, and its histological type.